Knowledge, attitude, and status of nitrite inhalant use among men who have sex with men in Tianjin, China - Zheng Zhang; Li Zhang; Feng Zhou; Zhen Li; Jie Yang (BMC, 2017)
Abstract Background Nitrite inhalants have become popular as recreational drugs among the homosexual population in some developed countries since the 1980s. These drugs, also called RUSH in China, have become attractive among Chinese men who have sex with men (MSM) in the past few years. The aim of this cross-sectional study was to understand the knowledge, attitude, and status of nitrite inhalant use among Chinese MSM. Methods The study participants were recruited from Tianjin, China between April and August 2012. Information, including demographics, sexual behavior, and RUSH use, was obtained through structured interviewer questionnaires. Blood samples were also collected to identify the status of HIV, HSV, and syphilis infections. Results A total of 500 participants were interviewed. Of the participants, 64.0% knew that RUSH could increase sexual pleasure and 38.6% of the participants had used RUSH at least once. The mean duration of RUSH use was 1.5 years. Among the participants who were familiar with RUSH, 60.0% had heard of RUSH for the first time after 2011, 55% received information about RUSH via the internet, and only 42.2% knew the side effects of RUSH. RUSH users were more likely to work in companies (Odds ratio [OR]: 2.61; 95% CI: 1.65-4.12), live with homosexual partners (OR: 1.88; 95% CI: 1.19-2.92), not live alone (OR: 2.26; 95% CI: 1.29-3.96), smoke cigarettes (OR: 1.49; 95% CI: 1.02-2.17), use alcohol (OR: 1.63; 95% CI: 1.12-2.39), and seek sexual partners on the internet (OR: 2.59; 95% CI: 1.50-4.50). Conclusions The impact of RUSH abuse on the expanding HIV epidemic among MSM has been demonstrated in China. Our findings suggest that the communication and awareness of health hazard of recreational drugs should be reinforced in HIV prevention education, especially through new media. Future research is needed to further explore how integrative strategies should be used to reduce the substance abuse and risky sexual behaviors.